Ototoxicity Monitoring: The Evolution of a Protocol for Head and Neck Cancer Patients - Jena Patel; Jacob Beiriger; Kalena Liu; Zach Urdang; Julia Croce; Molly Wolfson; Jacob Hulswit; Olivia Giglio; Jacob B. Hunter; Irina Middleton (OTO Open, 2025)
Abstract Objective We evaluated an ototoxicity monitoring program (OMP) for improving audiologic follow‐up in head and neck cancer (HNC) patients. Study Design Retrospective cohort study. Setting Tertiary academic center. Methods Two hundred and forty patients were recommended for chemotherapy between January 2017 and June 2022. An OMP was implemented in March 2021; every patient received an audiology referral and was contacted to schedule a pretreatment audiogram. Patients were divided into pre‐OMP and post‐OMP cohorts. Main outcome measures included rates of pretreatment audiograms, posttreatment audiograms, posttreatment otologic symptoms, and hearing aid utilization. Results There were 131 patients evaluated pre‐OMP and 109 evaluated post‐OMP. The mean age for all patients was 62.8 ± 11.9 years; 76.3% were male. After the implementation of the OMP, a significantly higher proportion of patients received a pretreatment audiogram (66.1% vs 34.4%, P < .001), with enrolled patients being 3.8 times more likely to obtain 1 (95% confidence interval: 2.2‐6.6), P < .001). There was a significant increase in reported otologic symptoms after implementing the program (18% vs 36%, P = .002). However, the rate of hearing aid utilization decreased after OMP implementation (pre‐OMP: 33% vs post‐OMP: 13%, P = .02). Conclusion Implementation of an OMP significantly improved the proportion of HNC patients that underwent pretreatment audiograms prior to systemic therapy; however, audiologic follow‐up remained largely unchanged in the posttreatment period. Level of Evidence Level 4.